2017
DOI: 10.1177/1745505717740218
|View full text |Cite
|
Sign up to set email alerts
|

Is ulipristal acetate the new drug of choice for the medical management of uterine fibroids? Res ipsa loquitur?

Abstract: Ulipristal acetate (Esmya © ) has been hailed the new wonder drug with regard to the medical management of uterine fibroids, and many postulate that it will remove the need for surgical treatment in the future. While the results from the PEARL studies are certainly promising and its amenorrhoeic rates and reduction in fibroid size are unquestionable, there is still a paucity of data with regard to its long-term effects, the effects on its usage prior to surgery and its variable efficacy in different ethnic pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…[14] However, although the data are limited and based mainly on surgical experience, many surgeons avoid the preoperative use of GnRH analogs as there are concerns regarding the distortion of the fibroid capsule with a resultant loss of surgical planes making the surgery more difficult and time-consuming with a resultant potential increased risk of recurrence. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, although the data are limited and based mainly on surgical experience, many surgeons avoid the preoperative use of GnRH analogs as there are concerns regarding the distortion of the fibroid capsule with a resultant loss of surgical planes making the surgery more difficult and time-consuming with a resultant potential increased risk of recurrence. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…The appropriateness of employing an antiprogestin-activated transactivator in a RCCV-based vaccine may need to be re-evaluated in light of more recent developments. Pivotal clinical trials demonstrated that ulipristal is capable of reducing the size of uterine fibroids, resulting in marketing approvals of the ulipristal-containing drug Esmya (Gedeon Richter Plc, Budapest, Hungary) in Europe and Canada [43][44][45]. A typical treatment involves one or more treatment cycles of up to three months (5 mg/day of ulipristal taken orally).…”
Section: Additional Thoughts On the Antiprogestin Co-control Of Rccvsmentioning
confidence: 99%
“…10 They are more common in primigravida over 35 years of age due to responsive growth to ovarian steroid hormones, estrogen and progesterone and are rarely seen before puberty. 1,2 On physical examination around 42% of large fibroids (>5 cm) and 12.5% of smaller fibroids can be diagnosed. 12 The gold standard diagnostic criteria to evaluate their size, number, location, relationship with the area of placental insertion and vascularization in pregnant women is gray scale ultrasonography followed by Magnetic resonance imaging in complex and inconclusive cases.…”
Section: Myomas In Pregnancymentioning
confidence: 99%
“…In about 10% of cases they can present with various symptoms like pelvic pressure, pelvic pain, heavy menstruation, dysmenorrhea, increased urinary frequency and impaired fertility in 1-3% of women. [1][2][3][4][5] The intensity of these symptoms varies according to the location, size and number of fibroids. At times these symptoms can be severe enough to adversely affect the quality of life (QOL) causing substantial morbidity and significant economic and social impact.…”
mentioning
confidence: 99%